STRATEGI BRANDING KOPI TUTUR RASA MIDTOWN HOTEL SEBAGAI KAFE INKLUSIF - Achmad Derajat Waskito (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the branding strategy implemented by Kopi Tuturr Rasa at Midtown Hotel in building its positioning as an inclusive café. Kopi Tuturr Rasa was selected as the research object because it integrates inclusivity into its brand identity through the involvement of Deaf baristas, creating a distinctive service experience compared to conventional coffee shops. This research employs a qualitative approach using a case study method. The theoretical framework is based on Kotler and Keller's Brand Positioning, consisting of Point of Difference, Point of Parity, Substantiator (Reasons to Believe), and Brand Mantra. Data were collected through in-depth interviews, observations, and documentation. The findings reveal that Kopi Tuturr Rasa's branding strategy is developed through the integration of inclusivity into its brand identity, communication activities, and consistent service practices. Its positioning as an inclusive café is strengthened by the unique service experience provided by Deaf baristas, the fulfillment of professional coffee shop service standards, the tangible implementation of disability empowerment, and the company's consistent commitment to professionalism, equality, and inclusivity. The study concludes that successful brand positioning is determined not only by marketing communication activities but also by the consistent implementation of brand values, resulting in a relatively shared perception among management, baristas, and customers.